Sharp Bound for the Generalized $m$-Linear $n$-Dimensional Hardy-Littlewood-Pόlya Operator (Analysis in Theory and Applications, 2023)
In this paper, we calculate the sharp bound for the generalized $m$-linear $n$-dimensional Hardy-Littlewood-Pόlya operator on power weighted central and noncentral homogeneous Morrey spaces. As an application, the sharp bound for theHardy-Littlewood-Pόlya operator on power weighted central and noncentral homogeneous Morrey spaces is obtained. Finally, we also find the sharp bound for theHausdorff operator on power weighted central and noncentral homogeneous Morreyspaces, which generalizes the previous results.